مواءمة مخرجات التعليم واحتياجات سوق العمل دراسة تحليلية نموذج سورية خلال الفترة (2001-2010) - حجازي, حسن (Latakia University Journal - Economic and Legal Sciences Series, 2018)
لقد أثبتت الكثير من التجارب التنموية للدول أن تقدمها لم يتوقف على ما تمتلكه من موارد طبيعية ووسائل إنتاج بل اعتمد بالدرجة الأولى على نوعية الموارد البشرية التي أسهم التعليم في إعدادها وتكوينها وتأهيلها، وقوة عمل مدربة ومؤهلة مهنياً وقادرة على استيعاب التطور العلمي والتكنولوجي لوسائل الإنتاج. وإدراكاً من الحكومة السورية لهذه الحقيقة فقد اهتمت بالتعليم في مراحله كافة وازداد عدد الطلاب والخريجين فيه بشكل ملحوظ خلال فترة الدراسة والفترات السابقة وأدت هذه الزيادة إلى تغيير البنية التعليمية لقوة العمل، إلا أن هذا التغيير لم يكن بالمستوى المطلوب لتحقيق التنمية ودفعها قدماً لأسباب عدة منها: النمو السكاني المرتفع الذي دفع بأعداد كبيرة من الطلاب إلى المدارس على حساب النوعية، وعدم التنسيق بين المؤسسات التعليمية واحتياجات سوق العمل، مما دفع بأعداد من الخريجين إلى سوق العمل باختصاصات لم تلق رواجاً فيه، لذا يتوجب على الحكومة إعادة النظر في السياسة التعليمية في المرحلتين الثانوية والجامعية، وربطهما باحتياجات سوق العمل وفق خطة استراتيجية، تقوم على إيجاد نظام تعليمي فني ومهني قادر على تخريج كوادر بشرية متخصصة في حقول المعرفة المختلفة، تلبي احتياجات المجتمع الحالية والمستقبلية، بما يتلاءم مع تحقيق تنمية اقتصادية واجتماعية مستدامة، وتحسين نوعية التعليم العالي لمواكبة متطلبات المجتمع واحتياجات سوق العمل المتجددة باستمرار.Many of the development experiences of countries have shown that progress did not stop the best use of natural resources and means of production but relied primarily on the quality of human resources that contributed to education in their preparation, composition and rehabilitated, and lab0r force trained and qualified professionally and able to accommodate scientific and technological development of the means of production. Aware of the Syrian government of this fact has focused on education in the stages of all the number of students and graduates which increased significantly during the study and prior periods period This increase led to change the educational structure of the labor force, but this change was not at the required level to achieve development and pushed forward for several reasons, including: high population growth which prompted large numbers of students to schools on the expense of quality, and lack of coordination between educational institutions and the needs of the labor market, pushing the numbers of graduates to work the functions of the market have not been popular in it, so the government should reconsider the educational policy in the secondary stages and university, and linked to the needs of the labor market in accordance with the strategic plan, based on a technical and vocational education system that is capable of graduation human cadres specialized in various fields of knowledge, to meet current and future needs of society, in line with the economic and social sustainable development, and improving the quality of higher education to keep up with the requirements of society and the evolving needs of the labor market constantly.